Influenza and pneumococcal vaccination in Australian adults: a systematic review of coverage and factors associated with uptake. Issue 1 (December 2016) - Dyda, Amalie; Karki, Surendra; Hayen, Andrew; MacIntyre, C.; Menzies, Robert; Banks, Emily; Kaldor, John; Liu, Bette
Abstract Background In the absence of an adult vaccination register, coverage estimates for influenza and pneumococcal vaccination come from surveys and other data sources. Methods Systematic review and meta-analysis of studies examining vaccination coverage in Australian adults from 1990 to 2015, focusing on groups funded under the National Immunisation Program, and intervals prior to and following the introduction of universal funding. Results Twenty-two studies met the inclusion criteria; 18 used self-report to determine vaccination status. There were 130 unique estimates of coverage extracted. Among adults aged ≥65y, during the period of universal funding (1999-onwards), the summary estimate of annual influenza vaccination coverage from 27 point estimates was 74.8 % (95 % CI 73.4–76.2 %; range 63.9–82.4 %); prior to this period (1992–1998) from 10 point estimates it was 61.3 % (95 % CI 58.0–64.6 %; range 44.3–71.3 %). For the period of universal funding for pneumococcal vaccination (2005-onwards) the summary estimate for coverage was 56.0 % (95 % CI 53.2–58.8 %; range 51.2–72.8 %, 10 point estimates); prior to 2005 it was 35.4 % (95 % CI 18.8–52.0 %; range 15.4–45.2 %). Coverage for both vaccines was significantly higher following the introduction of universal funding. Influenza vaccination coverage in those aged 18–65 years with a medical indication was lower but data were not combined. Seven studies reported on Aboriginal Australians with three studies reporting five coverage estimates for influenza vaccination in adults ≥65 years (range 71 % - 89 %). Conclusions Adult influenza and pneumococcal vaccination coverage has increased since the introduction of universal funding, but remains sub-optimal, with pneumococcal coverage lower than influenza. Implications: This review highlights the need for more coverage data overall and in high risk groups, to support public health programs to improve coverage.